2012
DOI: 10.1128/aac.06057-11
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Activity of Ceftobiprole and Vancomycin in a Rat Model of Infective Endocarditis Caused by Methicillin-Resistant and Glycopeptide-Intermediate Staphylococcus aureus

Abstract: The therapeutic activity of ceftobiprole medocaril, the prodrug of ceftobiprole, was compared to that of vancomycin, daptomycin, and the combination of a subtherapeutic dose of ceftobiprole and vancomycin in a rat model of infective endocarditis due to methicillin-resistant Staphylococcus aureus (MRSA) (ATCC 43300) or glycopeptide-intermediate Staphylococcus aureus (GISA) (NRS4 and HIP 5836) strains. The minimum bactericidal concentrations of ceftobiprole, vancomycin, and daptomycin at bacterial cell densities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…At least 16 in vitro studies have explored synergy between vancomycin and β-lactams against MRSA isolates, [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] all but one of which found evidence of synergy in some or all of the tested strains (►Table 1). These studies varied in their methodology (checkerboard synergy testing or time-kill curves), types of strains tested (MRSA vs. hVISA vs. VISA) and the β-lactams used, but a consistent finding across nearly all the studies was synergistic bacterial killing in most but not all strains tested.…”
Section: In Vitro Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…At least 16 in vitro studies have explored synergy between vancomycin and β-lactams against MRSA isolates, [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] all but one of which found evidence of synergy in some or all of the tested strains (►Table 1). These studies varied in their methodology (checkerboard synergy testing or time-kill curves), types of strains tested (MRSA vs. hVISA vs. VISA) and the β-lactams used, but a consistent finding across nearly all the studies was synergistic bacterial killing in most but not all strains tested.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…The few studies that have assessed combinations of vancomycin with β-lactams in animal models have all found evidence of synergy. 56,61,65 Climo et al found faster sterilization of infection with vancomycin plus nafcillin in MRSA rabbit endocarditis and renal abscess models. 56 Ribes et al tested various combinations of linezolid, vancomycin, and imipenem in a murine peritonitis VISA model using time-kill curves, and found faster bacterial killing with vancomycin plus imipenem compared with vancomycin alone, in both strains tested.…”
Section: Animal Studiesmentioning
confidence: 99%
“…The values for MIC 50/90 are generally one to two dilutions lower with most studies reporting MIC 90 of 0.5 µg/ml [2,13,14,36] and likelihood of target attainment is anticipated to be high with q12h dosing. Postantibiotic effect and synergy have not been formally studied, but they are likely to occur in MSSA, since they have been demonstrated with MRSA [49].…”
Section: Staphylococcus Aureusmentioning
confidence: 98%
“…The clinical significance of the postantibiotic effect is not clear. Synergy with vancomycin for MRSA and VISA strains has been demonstrated both in vitro and in vivo, but the significance of these observations is also unclear [49].…”
Section: Staphylococcus Aureusmentioning
confidence: 98%
“…(42), (v) AMP (100 mg/kg, q8h, i.m.) plus CRO (10 mg/kg, q8h, s.c.) (41), and (vi) DAP (45.3 mg/kg, q24h, s.c.) (21,45) and VAN (120 mg/kg, q12h, s.c.) (47,48). A group of infected but untreated control animals was left along with the therapy group to show the end log 10 CFU per gram versus the baseline (t ϭ 0) untreated controls.…”
Section: Methodsmentioning
confidence: 99%